Efektivitas Model Pembelajaran STAD (Student Teams Achievement Divisions) terhadap Hasil Belajar dan I’timad Siswa pada Mata Pelajaran PAI - Awalia Putri Sofiya; Ahmad Khoiri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education plays a vital role in shaping individual quality, particularly in terms of attitude and behavioral development throughout life. In the context of Islamic Religious Education (IRE) learning, challenges are still evident among fourth-grade students at SD Negeri 1 Selokromo, such as some students’ learning outcomes are not optimal, and display low participantion and self-confidence. This study aims to evaluate the effectiveness of the STAD model in improving students’ learning outcomes and self-confidence in the fourth grade at SD Negeri 1 Selokromo. Using a quantitative approach and a quasi-experimental design of the nonequivalent control group type, the data were analyzed through non-parametric statistical tests. The results revealed a significant difference between the pretest and posttest scores in the experimental class, with Z = -4.284 and p = 0.000 (Wilcoxon test). A significant difference was also found between the experimental and control classes in terms of learning outcomes (Z = -5.964; p = 0.000) and students’ self-confidence scores (Z = -2.891; p = 0.004), based on the Mann-Whitney test. The average posttest score of the experimental group was 96, higher than that of the control group, which only reached 64. These findings confirm that the STAD model is effective in enhancing both learning outcomes and students’ self-confidence in PAI learning. Therefore, this model can serve as a relevant alternative in creating an active, collaborative, and meaningful learning environment at the elementary school level.